Pengaruh Kepemimpinan Transformasional, Budaya Organisasi, Komitmen Pegawai Terhadap Kinerja Pegawai (ASN Pemerintah Kota Pekalongan) - Achmad Afzan Arslan Djunaid; Mahirun; Danang Satrio (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
This examine aimed to decide and examine the have an impact on of Transformational leadership Organizational Culture, and Employee Commitment on Employee Performance in the Pekalongan City Government. The analytical tool for data processing uses multiple regression with hypothesis testing using the t statistical test. The data used is primary data through distributing questionnaires using a Likert Scale (5 alternative answers). Sampling used Proportional Random Sampling with a sample size of 309 employees in the Pekalongan City Government. The results of this research show that there is a significant positive influence on the Transformational Leadership variable on the Performance variable, and the Organizational Culture variable on the Performance variable, as well as the Employee Commitment variable on the Performance variable.